Covalent immobilization of enzyme on aminated woven poly (lactic acid) via ammonia plasma: evaluation of the optimum immobilization conditions. Issue 10 (June 2017) - Song, Ji Eun; Song, Wha Soon; Yeo, Sang Young; Kim, Hye Rim; Lee, So Hee
The present study aims to develop an immobilization support from woven poly (lactic acid) (PLA) and establish the optimum immobilization conditions for trypsin. Woven PLA was modified by ammonia-based plasma treatment in order to incorporate amine groups on its surface. X-ray photoelectron spectroscopy analysis showed that the N1s composition of PLA increased significantly, from 0.66% to 5.92%, after ammonia-based plasma processing. Trypsin from porcine pancreas was immobilized onto modified woven PLA by covalent binding after activating PLA with glutaraldehyde (GA). The results indicated that the optimal GA treatment conditions were as follows: pH of 10.0, 2% GA (v/v), and 180 min crosslinking time. In addition, the optimum immobilization conditions were as follows: pH of 8.5, 10% (owf) of trypsin concentration, 30 min, and 25℃. Under the optimum conditions, the amount of immobilized enzyme on woven PLA was 0.28 mg/mg and specific activity was 3.763 U/mg. In addition, the pH and thermal stabilities of the immobilized trypsin were improved. The immobilized trypsin retained approximately 55% of its initial activity after 20 days of storage and exhibited the potential for repetitive use through approximately 15 cycles. GA crosslinking and trypsin immobilization were found to improve the roughness of the PLA surface and increase its hydrophobicity. The data indicate that modified woven PLA, used as an immobilization support, shows suitable properties for use as a biocatalytic material in enzymatic applications.